Isolation of Endophytic Bacteria and Phytoremediation of Soil Contaminated with Polycyclic Aromatic Hydrocarbons Using Cajanus cajan and Lablab purpereus (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
Polycyclic aromatic hydrocarbons (PAHs) are among the major compounds posing environmental and health problems worldwide. In the present study, phytoremediation of PAHs using Cajanus cajan and Lablab purpereus in addition to isolation of endophytic bacteria associated with the plant tissues was undertaken. Soil samples contaminated with PAHs were collected from a mechanic workshop in Sokoto metropolis and analysed using standard laboratory procedures. Seeds of the two plants species were sown in the contaminated soil and irrigated for eight weeks to determine the plants’ ability to remediate PAHs. Bacterial count revealed that the plants’ tissues contained 2.3×104 cfu/g and 2.7×104 cfu/g of endophytes. The endophytes were identified to be the members of Pseudomonas, Micrococcus, Bacillus, Rhodococcus and Flavobacterium. GC-MS analysis revealed that the soil samples contained 19.21 ppm PAHs, which were reduced to 2.34 ppm (12.18%) and 4.88 ppm (25.40%) in soils treated with C. cajan and L. purpureus, respectively. Naphthalene was completely degraded in both cases, whereas pyrene, flourene and flouranthene were either completely degraded or significantly reduced. Only indeno (1,2,3 cd) pyrene was least degraded with more than 50% residual concentration. Therefore, the plant species was considered as an important tool in the remediation of PAHs contaminated soil and the role of their endophytes in degradation was thoroughly investigated.
Keywords: PAHs, Phytoremediation, Cajanus cajan, Lablab purpureus, endophyte